2017
DOI: 10.1152/ajpregu.00171.2017
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of leptin in systemic inflammation: a study targeting physiological leptin levels in rats and their macrophages

Abstract: To elucidate the role of leptin in acute systemic inflammation, we investigated how its infusion at low, physiologically relevant doses affects the responses to bacterial lipopolysaccharide (LPS) in rats subjected to 24 h of food deprivation. Leptin was infused subcutaneously (0-20 μg·kg·h) or intracerebroventricularly (0-1 μg·kg·h). Using hypothermia and hypotension as biomarkers of systemic inflammation, we identified the phase extending from 90 to 240 min post-LPS as the most susceptible to modulation by le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…By culturing freshly excised resident macrophages under identical conditions, our intention was to eliminate their modulation by extrinsic factors that make up the distinct tissue microenvironment of obese vs. lean animals. Such factors include hormones with immunomodulatory actions (17, 30, 31), in addition to cytokines, lipid-derived mediators and gaseous transmitters (32). In the absence of such factors, diet-dependent changes in macrophage biology likely reflect reprogramming of their intrinsic properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By culturing freshly excised resident macrophages under identical conditions, our intention was to eliminate their modulation by extrinsic factors that make up the distinct tissue microenvironment of obese vs. lean animals. Such factors include hormones with immunomodulatory actions (17, 30, 31), in addition to cytokines, lipid-derived mediators and gaseous transmitters (32). In the absence of such factors, diet-dependent changes in macrophage biology likely reflect reprogramming of their intrinsic properties.…”
Section: Discussionmentioning
confidence: 99%
“…One way to dissect out these factors is to extract macrophages from the distinct tissue microenvironments of obese vs. lean animals, so that they can be subsequently studied ex vivo under identical conditions. Using this sort of approach, we have observed that even a brief change in energy balance (24 h of food deprivation) is able to reprogram the intrinsic responsiveness to LPS in certain macrophage subpopulations (17). Thus, prominent changes in the intrinsic program of macrophages to LPS can be expected in obese animals chronically maintained on a high-fat diet (HFD).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, neutrophil adhesion to vascular endothelial cells inhibited the production of NO, as determined by the aggravation of cell edema (74). Leptin has an anti-inflammatory role (75,76); it activates the nuclear factor-κB pathway, inhibits the expression of pro-inflammatory factors [tumor necrosis factor (TNF)-α, IL-6, IL-1β] within 7 h and increases the expression of IL-10 (74,77) Within 100 min, the human body is able to recover from hypothermia and hypotension caused by ischemia/reperfusion injury (78). Within 90–240 min, TNF-α is inhibited.…”
Section: Protective Mechanisms Of Leptin In the Brainmentioning
confidence: 99%
“…Physiological levels of leptin result in selective suppression of TNFa in macrophage subpopulations by food withdrawal as a centrally mediated anti-inflammatory effect, which is incompletely understood [149].…”
Section: Morbid Obesitymentioning
confidence: 99%